2008
DOI: 10.1097/ico.0b013e31815a50bf
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Aberration Changes After Laser In Situ Keratomileusis Performed With Mechanical Microkeratome and IntraLase Femtosecond Laser: 1-Year Follow-up

Abstract: Wavefront corneal aberrations change significantly 1 year after myopic LASIK performed with the Hansatome microkeratome as well as with IntraLase femtosecond lasers. Both of the procedures induce higher-order aberrations in the anterior corneal surface, but the amount of comalike aberration increases more with the Hansatome mechanical microkeratome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…Although studies have analyzed changes in the short and medium term after LASIK (3 to 36 months), 6,7,9,[14][15][16][17][18][19] to our knowledge, there are no long-term studies of the differences between LASIK flap creation with a femtosecond laser and LASIK flap creation with a microkeratome. The purpose of this randomized study was to assess the differences in visual and optical performance 4 years after LASIK in which the flap was created with 1 of these methods.…”
Section: Discussionmentioning
confidence: 89%
“…Although studies have analyzed changes in the short and medium term after LASIK (3 to 36 months), 6,7,9,[14][15][16][17][18][19] to our knowledge, there are no long-term studies of the differences between LASIK flap creation with a femtosecond laser and LASIK flap creation with a microkeratome. The purpose of this randomized study was to assess the differences in visual and optical performance 4 years after LASIK in which the flap was created with 1 of these methods.…”
Section: Discussionmentioning
confidence: 89%
“…The results showed that total HOAs and spherical aberration after LASIK with the mechanical microkeratome were significantly higher than those after LASIK with the femtosecond laser. In comparison of total aberrations, the SD of the mechanical microkeratome group was much higher than that of the femtosecond laser group in a study by Buzzonetti et al, 27 which suggests their data might include outliers. Thus, we excluded their data to examine the effect without Buzzonetti et al, and the result was still statistically significant (mean difference À0.03 mm; 95% CI, À0.05 to À0.01; PZ.003).…”
Section: Discussionmentioning
confidence: 95%
“…Three trials 16,24,27 including 289 eyes reported corneal aberration values (mean G SD) in micrometers but at different optical zone diameters (3.0 mm, 27 3.5 mm, 24 and 4.0 mm 16 ). The forest plot showed that 6 months or more after surgery, the mechanical microkeratome group was associated with greater total and spherical aberration values than the femtosecond laser group with the exception of Calvo et al 16 Analysis of these data found statistically significant differences between groups in favor of the femtosecond laser ( Figure 5).…”
Section: Higher-order Aberrations Derived From the Anterior Corneal Smentioning
confidence: 98%
See 1 more Smart Citation
“…53,54 Contradicting these results, other studies show that the femtosecond procedure provided better optical and visual outcomes after surgery by reducing the induction of corneal HOAs. 55,56 Considered together, these results allow us to assert that the induction of corneal aberrations is dependent on several factors, including the type of excimer laser refractive surgery procedure, pupil size, amount of correction, ablation profile, and flap quality.…”
Section: Corneal Wavefront Analysis In Excimer Laser Refractive Surgerymentioning
confidence: 95%